REVIEW: AGNIA GRIGAS, THE POLITICS OF ENERGY AND MEMORY BETWEEN THE BALTIC STATES AND RUSSIA - Karmazinaitė, Sabina (Baltic Journal of Political Science, 2013)
Since the declarations of independence more than 20 years ago, besides others, the Baltic states are being pursued by energy dependency issues. Differently than was wishfully expected, accession to the EU and NATO for Estonia, Latvia, and Lithuania did not mean suddenly improved relations with Russia, overcome domestic political weaknesses as well as fast solutions in the energy security sector. They still cause a notable predicament after accession to the EU and NATO. In the recent years, an especial focus on the energy sector could be observed in the Baltic states – energy security has become one of the main concerns for politicians and attracts a lot of attention in the Baltic media and public debates. However, when looking from the academic perspective and analysis, these issues seem not to have found their place among more serious and consistent scholarly interests, creating a strange paradoxical situation when constant daily topicalities in the media and political life were left behind a deeper academic analysis. [...]